Factors influencing volunteer tourism awareness among university students in Universiti Malaysia Kelantan city campus - Nuratika Dolkefli; Nurulhuda Najihah Md Isa; Nurul Azarina Azfahani Mohd Aris; Syazwani Sahwandi (2021)
This study aims to identify the determinants of volunteer tourism awareness among university students in University Malaysia Kelantan City Campus, particularly in terms of their awareness in volunteer tourism. To achieve the best research outcome, the researchers outlined three objectives in this study: (i) to examine the relationship between attitudes and volunteer tourism awareness among university students in University Malaysia Kelantan City Campus; (ii) to examine the relationship between social influence and volunteer tourism awareness among university students in University Malaysia Kelantan City Campus; and (iii) the relationship between perceived behavioral control (PBC) and volunteer tourism awareness among university students in University Malaysia Kelantan City Campus. For data collection, the researchers used primary data including a convenience sampling method to select a total of 359 university students in University Malaysia Kelantan City Campus. Quantitative data collection through questionnaires that comprise three sections was employed to help the researchers obtain continuous data and subsequently perform data analysis to achieve the objectives addressed in this study. Overall, awareness of voluntary tourism, attitudes, social influence, and perceived behavioral control (PBC) is the marketing tourism factors believed to influence voluntary tourism awareness among university students in University Malaysia Kelantan City Campus.